Kesiapan Pemerintah Kota Surakarta Dalam Menyiapkan Usaha Mikro, Kecil, dan Menengah (UMKM) Kota Surakarta untuk Menghadapi Masyarakat Ekonomi Asean 2015 Melalui Kebijakan Merek - Alexander A Kurniawan (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2016)
The study concluded that Law No. 20 Year 2008 on Micro, Small andMedium Enterprises (Act MSMEs) and Law No. 7 Thahun 2014 on Trade (Act ofTrade), Government Central Government and Local Government needs to empower theSMEs one aspect that needs to be done, namely aspect Trade Promotion whichregulates the ownership of the facilitation of Intellectual Property Rights in particular isa Trademark. Therefore, Surakarta or Solo as one of the regional government inIndonesia has also issued Regional Regulation No. 5 of 2014 About EmpoweringSMEs as a follow-up of the SME Act and the Commerce Act. But the Department ofCooperatives and SMEs as the official responsible for the empowerment of SMEsSurakarta do not have a specific policy to prepare SMEs in the face of MEA whichwill take effect at the end of December 2015 through the facilitation of the ownership ofIPR in particular the right to Brand. During this time, policy facilitation TrademarkRights in Surakarta is only intended for Small and Medium Industries (SMI) is notfor SMEs, facilitation was issued by the Department of Industry and Trade.